PENINGKATAN KUALITAS LAYANAN PUBLIK MELALUI PELAYANAN ADMINISTRASI PERNIKAHAN PADA KANTOR URUSAN AGAMA KECAMATAN WOLIO KOTA BAU BAU - Adrian Tawai; Muhammad Yusuf; Muh. Rijal (Journal Publicuho, 2022)
This study aims to determine the marriage administration services at the Religious Affairs Office (KUA) Wolio District Bau-Bau City and to determine the factors of marriage administration services at the Religious Affairs Office (KUA) Wolio District Bau-Bau City. It uses observation, interviews, and documentation as a qualitative descriptive research method. The results of this study indicate that the marriage administration services carried out by the Office of Religious Affairs (KUA) of Wolio District are carried out by paying attention to simple, transparent, complete and affordable aspects. everything is done to make it easier for the community to manage the existing marriage administration and in terms of being transparent, information about the arrangement is given, including using social media and in complete terms where the people who come to take care must pay attention to all the completeness of the files in managing and affordable and affordable. In terms of costs, where everything has been regulated in the existing rules, people who take care of marriage administration are charged six hundred thousand for those who get married outside the office and for those who get married at the Wolio District Religious Affairs Office (KUA) with a note that it is done within working time.